Systemic Capillary Leak Syndrome: Is Methylene Blue the Silver Bullet? - Michele Umbrello; Marco Gardinali; Davide Ottolina; Giancarlo Zanforlin; Gaetano Iapichino (Case Reports in Critical Care)
Background. Systemic capillary leak syndrome (SCLS) is a rare disorder characterized by unexplained, recurrent episodes of transient, abrupt increase in endothelial permeability, leading to severe hypotension, generalized edema, and hemoconcentration. Case Report. We report the case of a patient suffering from systemic capillary leak syndrome and present a possible interpretation of the pathophysiology of this condition. Besides the classical triad of hypotension, edema, and hemoconcentration, we recorded increased levels of methemoglobin, an index of NO overproduction. We present a possible interpretation of the pathophysiology of this condition based on the fast and complete reversal of symptoms after methylene blue administration (which opposes NO-induced effects) and speculate that increased NO levels could be implicated in the pathophysiology of the capillary leak phase. Why should an emergency physician be aware of this? The safety of this treatment and its fluid- and cathecolamine-sparing effect deserve consideration and further research.